Kepatuhan Jumantik Rumah dalam Mengisi Kartu Jentik Sebagai Upaya Surveilans Vektor DBD di Kecamatan Pondok Aren Kota Tangerang Selatan - Hubullah Fuadzy; Heni Prasetyowati; Endang Puji Astuti (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2020)
Control form in one house one Jumantik program can be a vector surveillance media. The implementation of the control form has many obstacles. This study described the compliance of Jumantik in filling control form in high and low dengue case area in South Tangerang. Quantitative data were obtained using a closed questionnaire with 268 respondents. Qualitative data were obtained from in-depth interviews with 10 selected informants. Variables in the form of characteristics, knowledge, attitudes and actions were analyzed using the Mann Whitney test to see group differences, while qualitative analysis by identifying potential and motivation for compliance in filling control form which is categorized into Strengtness, Weakness, Opportunity, Threat (SWOT) analysis. The results show that most of the respondents are women who in productive age. Most of the respondents knew the form and benefits of the control form (p-value 0.101; 0.248), but respondents didn’t know who filled out the forms (p-value 0.636). These results did not differ significantly between low and high DHF case groups, these results were the same as the analysis of attitude variables (p-value 0.254 and 0.636). The action analysis showed that there were differences in the routine practice of filling and checking control forms between the low and high case groups (p-value 0.000; 0.005) as well as the implementation of G1R1J socialization (p-value 0.000). House larva monitoring obedience to fill control form in areas with low Dengue cases is better than in areas with high Dengue cases. The challenges in filling control form were lack of facilities, old age of staff, visual impairment, busyness, and forgetfulness.